Homeless Patients Associate Clinician Bias With Suboptimal Care for Mental Illness, Addictions, and Chronic Pain - Cyndi Gilmer; Kristy Buccieri (SAGE Publishing, 2020)
Objective: To determine how accessible health care services are for people who are experiencing homelessness and to understand from their perspectives what impact clinician bias has on the treatment they receive. Methods: Narrative interviews were conducted with 53 homeless/vulnerably housed individuals in Ontario, Canada. Visit history records were subsequently reviewed at 2 local hospitals, for 52 of the interview participants. Results: Of the 53 participants only 28% had a primary care provider in town, an additional 40% had a provider in another town, and 32% had no access to a primary care provider at all. A subset of the individuals were frequent emergency department users, with 15% accounting for 75% of the identified hospital visits, primarily seeking treatment for mental illness, pain, and addictions. When seeking primary care for these 3 issues participants felt medication was overprescribed. Conversely, in emergency care settings participants felt prejudged by clinicians as being drug-seekers. Participants believed they received poor quality care or were denied care for mental illness, chronic pain, and addictions when clinicians were aware of their housing status. Conclusion: Mental illness, chronic pain, and addictions issues were believed by participants to be poorly treated due to clinician bias at the primary, emergency, and acute care levels. Increased access to primary care in the community could better serve this marginalized population and decrease emergency department visits but must be implemented in a way that respects the rights and dignity of this patient population.